Implementación de un sistema de adquisición de datos para el análisis de calidad de energía del inversor de una estación fotovoltaica de 2 kw. - Acosta Villalva, Stalin Enrique (2022)
The objective of this technological proposal is to implement a data acquisition system for the analysis of the power quality of the inverter of a 2 kW photovoltaic station, by recording measurements of the electrical parameters of the photovoltaic inverter, to determine the behavior of the voltage and current waves connected to a load under normal operating conditions. The study arises from the energy distortion of voltage and current in the single-phase inverter produced by the harmonics of the loads, limiting the monitoring of electrical parameters, as well as maintenance actions after the years of operation of the equipment. The methodology used is of an applicative nature with the use of bibliographic, field, inductive, deductive methods and the CVM-A1500 equipment. The results during the records made based on the ARCENNR 002/20 regulation and the IEEE 519-2014 regulation, in a period of 15 minutes, on July 26, 2022, from 9:00 a.m. to 11:15 a.m. Where the inverter offers an average voltage of 125.96 V and an average current of 6.15 A, THDv of 4.16% and THDi 4.45%. In the recording of July 27, 2022 from 12:00 p.m. to 2:15 p.m., an average voltage of 127.45 V and an average current of 4.07 A, THDv of 4.24% and THDi 36.61% were obtained. In the recording of July 28, 2022 from 7:45 a.m. to 10:00 a.m., an average voltage of 124.26 V and an average current of 12.01 A were obtained, THDv of 3.78% and THDi 3.95%, of According to each of the analyzes carried out, the result is within the limit of the established regulations of (8%) for voltage and (5%) for low voltage current, but nevertheless in the record of July 27, 2022, the THDi is outside the limits established by the regulations in relation to the fundamental current. Among the conclusions, it stands out that the inverter connected to certain non-linear loads presents voltage and current harmonics, which affect the power factor, and the operating performance of the inverter of the photovoltaic station.